Inhibit a kinase to degrade a histone demethylase: a candidate therapeutic approach in glioblastoma - Maiques-Diaz, Alba; Somervaille, Tim C. P. (Translational Cancer Research, 2017)
Lysine-specific histone demethylase 1A (KDM1A; more commonly known as LSD1), the first enzyme discovered to possess histone demethylase activity, removes monomethyl and dimethyl groups from histone H3 lysine 4 (H3K4) (1). It is generally considered a transcription repressor being a key component of corepressor complexes such as CoREST and NuRD (2-4). High level expression of KDM1A protein is observed in multiple cancer types, including poor prognosis sub-groups of prostate, lung, brain and breast cancer, as well as in certain hematological malignancies. Pharmacologic inhibitors of KDM1A are currently in early phase clinical trials (4).